syms k a
L=3.3*10^(-6);
C=20*10^(-12);
[w]=solve('k=1/2*sqrt((50^2*(100^2+(w*L-1/(w*C))^2))/(100^2+(w*L-1/(w*C)^2)^2))*cos(a)')
结果
w =
RootOf(625*C^4*L^2*X1683^6*cos(a)^2 - C^4*L^2*X1683^6*k^2 - 1250*C^3*L*X1683^4*cos(a)^2 + 6250000*C^4*X1683^4*cos(a)^2 - 10000*C^4*X1683^4*k^2 + 2*C^2*L*X1683^3*k^2 + 625*C^2*X1683^2*cos(a)^2 - k^2, X1683)
我以为是阶次太搞 变幻下式子
syms k a L C
[w]=solve('2*k/(50*cos(a))=sqrt(1/(100^2+(1/(w*C)-w*L)^2))','w')
结果是
w =
((- 10000*C^2*k^2 + 625*C^2*cos(a)^2 + 4*L*C*k^2)^(1/2) + 25*C*(cos(a) - 4*k)^(1/2)*(4*k + cos(a))^(1/2))/(2*C*L*k)
-((- 10000*C^2*k^2 + 625*C^2*cos(a)^2 + 4*L*C*k^2)^(1/2) + 25*C*(cos(a) - 4*k)^(1/2)*(4*k + cos(a))^(1/2))/(2*C*L*k)
((- 10000*C^2*k^2 + 625*C^2*cos(a)^2 + 4*L*C*k^2)^(1/2) - 25*C*(cos(a) - 4*k)^(1/2)*(4*k + cos(a))^(1/2))/(2*C*L*k)
-((- 10000*C^2*k^2 + 625*C^2*cos(a)^2 + 4*L*C*k^2)^(1/2) - 25*C*(cos(a) - 4*k)^(1/2)*(4*k + cos(a))^(1/2))/(2*C*L*k)
但是验证结果不对啊 还是严重失真???????
L=3.3*10^(-6);
C=20*10^(-12);
[w]=solve('k=1/2*sqrt((50^2*(100^2+(w*L-1/(w*C))^2))/(100^2+(w*L-1/(w*C)^2)^2))*cos(a)')
结果
w =
RootOf(625*C^4*L^2*X1683^6*cos(a)^2 - C^4*L^2*X1683^6*k^2 - 1250*C^3*L*X1683^4*cos(a)^2 + 6250000*C^4*X1683^4*cos(a)^2 - 10000*C^4*X1683^4*k^2 + 2*C^2*L*X1683^3*k^2 + 625*C^2*X1683^2*cos(a)^2 - k^2, X1683)
我以为是阶次太搞 变幻下式子
syms k a L C
[w]=solve('2*k/(50*cos(a))=sqrt(1/(100^2+(1/(w*C)-w*L)^2))','w')
结果是
w =
((- 10000*C^2*k^2 + 625*C^2*cos(a)^2 + 4*L*C*k^2)^(1/2) + 25*C*(cos(a) - 4*k)^(1/2)*(4*k + cos(a))^(1/2))/(2*C*L*k)
-((- 10000*C^2*k^2 + 625*C^2*cos(a)^2 + 4*L*C*k^2)^(1/2) + 25*C*(cos(a) - 4*k)^(1/2)*(4*k + cos(a))^(1/2))/(2*C*L*k)
((- 10000*C^2*k^2 + 625*C^2*cos(a)^2 + 4*L*C*k^2)^(1/2) - 25*C*(cos(a) - 4*k)^(1/2)*(4*k + cos(a))^(1/2))/(2*C*L*k)
-((- 10000*C^2*k^2 + 625*C^2*cos(a)^2 + 4*L*C*k^2)^(1/2) - 25*C*(cos(a) - 4*k)^(1/2)*(4*k + cos(a))^(1/2))/(2*C*L*k)
但是验证结果不对啊 还是严重失真???????